Table of Content - - (Journal of Educational and Psychological Sciences, 2024)
Table of Content:1. Developing Primary School Management in the Kingdom of Saudi Arabia based on Self-management: Proposed ModelProf. Fatima Abdullah Al-Bishr, Ibtisam Wajib Alotaibi, Sarah Abdullah Alsuwaie2. The effect of different patterns of digital storytelling (visual and audio) on enhancing Imaginary capabilities and Creative thinking of science studies of the second gradeNajma Nasser Salim Al-Jabri3. Association between personality traits and psychological burnout among the Coaches of First-Class teams and Unions in MuscatDr. Salim Mohammed Ali Al-Ghailani4. The Effectiveness of the Reality Counseling Program in Improving the Self-Esteem of Adolescents from Divorced FamiliesDr. Hany Ibrahim Elshamy, Mohamed Kamal Abdelrahman, Mahmoud Abdelaziz Eliwa5. Work rotation and its role in getting rid of job burnout as the administrative assistant in middle-stage schools at east of JeddahManal Jaza Alotaibi, Prof. Najat Mohammed Saeed Alsaigh6. Exploring the Utilization of Artificial Intelligence on Educational Efficiency: A Case Study in RiyadhMrs. Sarah Hamoud Al-Kahtani
Keywords: Journal of Educational and Psychological Sciences